Prognostic Value of Total Bilirubin in Patients With ST-Segment Elevation Acute Myocardial Infarction Undergoing Primary Coronary Intervention - Zhao, Xiaoxiao; Wang, Ying; Liu, Chen; Zhou, Peng; Sheng, Zhaoxue; Li, Jiannan; Zhou, Jinying; Chen, Runzhen; Chen, Yi; Zhao, Hanjun; Yan, Hongbing (Frontiers in Cardiovascular Medicine, 2020)
Background: Bilirubin, a natural product of heme catabolism, demonstrates antioxidant and anti-inflammatory activities and is inversely associated with stable coronary artery disease. However, the relation between bilirubin levels and long-term outcomes in patients with ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PPCI) is still unknown. This study aimed to establish a score model based on bilirubin for predicting MACE and to stratify patients to the level of care. Methods and Results: Data from 4,151 consecutive STEMI patients who underwent PPCI were evaluated, and 3,708 cases were analyzed. Total bilirubin (TBil) was measured during admission, and the study population was divided into two groups. The high TBil group (n=143) was defined as patients having ≥22 µmmol/L and the low TBil group (n=3,565) as patients having any value in the lower level, i.e., <22 µmmol/L. The median follow-up period was 754 days (2.066 years). The major adverse cardiovascular event (MACE) was significantly lower in the high TBil group than in the low TBil group (3.5% vs. 11.0%, p=0.001). In the multivariate Cox analyses, a significant association was noted between TBil levels and the adjusted risk of MACE (hazard ratio, 0.279; 95% confidence interval, 0.088–0.877; p=0.029). A prediction score model composed of TBil, age, hypertension history, and other eight variables was developed, with scores ranging from 0 to 500. The scores identified patients as low, medium, and high-risk categories. The cumulative survival rate was significantly higher in the low-risk group than in the medium-risk group and high-risk group for MACE, all-cause death, cardiac death, recurrent myocardial infarction, and ischemic stroke (p<0.001, p<0.001, p<0.001, p=0.030, p=0.001, respectively). The area under the curve of the TBil score was 0.768 and significantly greater in the pairwise comparison with Global Registry of Acute Coronary Events score (p=0.0012). Conclusion The TBil-based score model can be used to predict MACE in patients with STEMI undergoing PPCI.